Active fire safety measures in the heritage timber buildings in Malaysia - Salleh, Nurul Hamiruddin; Mohtar, Mohd Alif Wajdi (Malaysian Institute of Planners (MIP), 2020)
Malaysia has a significant amount of heritage timber buildings located in every part of the country. The buildings symbolised the origin of the country’s vernacular architectural style as well as the historical representation of the local community culture and its surrounding context. However, due to the combustible nature of timber, these heritage timber buildings are highly exposed to the risks of fire. Currently, there are no proper fire safety guidelines specifically for heritage buildings which can act as a good reference for the building owners or conservators in safeguarding the heritage buildings. The purpose of this study is to identify existing active fire safety measures in selected heritage timber buildings in Malaysia. The study was conducted through literature findings and observation of four selected heritage timber buildings. The study had identified that all four heritage timber buildings were equipped with very basic active fire safety measures.